2022
DOI: 10.1007/s11356-022-19352-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sectoral decompositions of electricity consumption on economic growth in India: evidence from SVAR framework

Abstract: This study examine the effects of electricity consumption from different sectors such as agricultural, commercial, domestic, Industrial (HV), Industrial (LV-MV) and Miscellaneous sector on economic growth over the period of 1981-2019 in case of India. We used SVAR framework and concluded that the consumption of electricity from agriculture sector has a negative impact on economic growth. Whereas, the Industrial (HV and MV-LV) and commercial electricity consumption have positive impact on economic growth. Simil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In another study panel, VAR was used to analyze the causal relationship between government debt and economic growth for a sample of 20 developed countries and found a negative relation between the two variables (Lof and Malinen, 2014). Bal et al (2022) used SVAR to analyze the impact of electricity consumption on economic growth.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In another study panel, VAR was used to analyze the causal relationship between government debt and economic growth for a sample of 20 developed countries and found a negative relation between the two variables (Lof and Malinen, 2014). Bal et al (2022) used SVAR to analyze the impact of electricity consumption on economic growth.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A significant portion of these studies is pertinent to environmental degradation. For instance, Abbasi et al (2021) for Pakistan, Bal et al (2022) for India, stated that electricity consumption increased CO2 emissions, and all those studies indicated the significant impacts of energy consumption on environmental degradation. Moreover, according to , it is clear that due to its large market share, Bitcoin also demands a high amount of energy during the validation and mining processes.…”
Section: Introductionmentioning
confidence: 99%